Cyber-attacks against companies in Germany: results of a representative company survey 2018/2019 - Dreißigacker, Arne (Forschungsbericht / KFN, Kriminologisches Forschungsinstitut Niedersachsen e.V., 2020)
This research report is an English translation of the German language KFN Research Report No. 152. 1 lt is not excluded that this English version may therefore contain deviations in explanations or meanings which are caused by the translation process.